Pengaruh Media Audio Visual Dan Motivasi Terhadap Kemampuan Berbicara Siswa Sekolah Dasar - Yadi, Fathul; Padlurrahman, Padlurrahman; Murcahyanto, Hary (Educatio, 2024)
The use of audio-visual media in the learning process is one of the plans that a teacher has prepared to make the learning process more interesting and can motivate students to learn. Through audiovisual media, children have new experiences in improving their speaking skills. The aim of this research is to determine the effectiveness of using audio-visual media on the speaking abilities of fifth grade elementary school students at SDN 2 Teko. The design of this research is experimental research in the form of a Quasi Experimental Design in the form of Nonequivalent Control Group Design where two groups of subjects are given different treatments for a certain period of time. The subjects of this research were 20 class V students at SDN 2 Teko as an experimental class who used audio visual media in the learning process and 24 class V students at SDN 2 Teko as a control class who did not use audio visual media in the learning process. The statistical analysis used is product moment correlation for validity testing and Cronbach's alpha for instrument reliability testing. Lilliefors method to test data normality, Levene method to test homogeneity and t test to test hypotheses. All calculations were processed using the SPSS version 16 program. The results of this research on students' speaking abilities show that the average initial test score in the experimental class is 5.9 and the control class is 6.1, while the average final test score in the experimental class is 7.9 and the control class is 6.9. As for the N-Gain results of speaking ability, the average gain or increase in learning outcomes from pre-test to post-test reached 0.6 in the medium category. These data show that learning using Audio Visual media influences the results of learning to speak by telling stories in Indonesian language subjects in class V elementary school.